The Influence of Social Intellect on the Features of the Behavior of Cadets Studying at Institutions With Specific Learning Conditions in Frustration and Stress Situations - S. V. Kharchenko (Law and Safety)
Professional communication of a police officer often occurs in complicated conditions, frustration and stress. The influence of the factor of “social intelligence” on the features of communication in ordinary conditions of future specialists in the professions “man – man” is actively studied in psychological science. The objective of this study was to summarize empirical data on the interrelationships between social intelligence abilities and behavior patterns in the frustration and stress situation of cadets of higher educational institutions with specific learning conditions.